Spectral density mapping at multiple magnetic fields suitable for (13)C NMR relaxation studies - Kadeřávek, Pavel; Zapletal, Vojtěch; Fiala, Radovan; Srb, Pavel; Padrta, Petr; Přecechtělová, Jana Pavlíková; Šoltésová, Mária; Kowalewski, Jozef; Widmalm, Göran; Chmelík, Josef; Sklenář, Vladimír; Žídek, Lukáš (Journal of magnetic resonance (San Diego, Calif., 2016)
Standard spectral density mapping protocols, well suited for the analysis of (15)N relaxation rates, introduce significant systematic errors when applied to (13)C relaxation data, especially if the dynamics is dominated by motions with short correlation times (small molecules, dynamic residues of macromolecules). A possibility to improve the accuracy by employing cross-correlated relaxation rates and on measurements taken at several magnetic fields has been examined. A suite of protocols for analyzing such data has been developed and their performance tested. Applicability of the proposed protocols is documented in two case studies, spectral density mapping of a uniformly labeled RNA hairpin and of a selectively labeled disaccharide exhibiting highly anisotropic tumbling. Combination of auto- and cross-correlated relaxation data acquired at three magnetic fields was applied in the former case in order to separate effects of fast motions and conformational or chemical exchange. An approach using auto-correlated relaxation rates acquired at five magnetic fields, applicable to anisotropically moving molecules, was used in the latter case. The results were compared with a more advanced analysis of data obtained by interpolation of auto-correlated relaxation rates measured at seven magnetic fields, and with the spectral density mapping of cross-correlated relaxation rates. The results showed that sufficiently accurate values of auto- and cross-correlated spectral density functions at zero and (13)C frequencies can be obtained from data acquired at three magnetic fields for uniformly (13)C-labeled molecules with a moderate anisotropy of the rotational diffusion tensor. Analysis of auto-correlated relaxation rates at five magnetic fields represents an alternative for molecules undergoing highly anisotropic motions.
Keywords: Magnetic field; Signal Processing, Computer-Assisted; Nucleic acids; Sensitivity and Specificity; senzitivita a specificita; Nuclear magnetic resonance; Carbohydrates; Algorithms; Spectral density function; počítačové zpracování signálu; magnetická rezonanční spektroskopie s uhlíkem 13C; magnetické pole; Relaxation; reprodukovatelnost výsledků; RNA, Small Interfering; malá interferující RNA; Data Interpretation, Statistical; Reproducibility of Results; algoritmy; Magnetic Fields; Carbon-13 Magnetic Resonance Spectroscopy; interpretace statistických dat